GAMBARAN PENGETAHUAN STAKEHOLDER TENTANG STUNTING DALAM UPAYA PERCEPATAN DESA EMAS DI KABUPATEN MOJOKERTO - Ni Njoman Juliasih; Eko Budi Santoso; Ade Lia Ramadani; Sugiharto (Universitas Airlangga, 2022)
Stunting is a chronic nutritional problem caused by cumulative and continuous malnutrition resulting in children being too short for their age. The percentage of stunted under-five children in 2021 in East Java province was 23.5%. Meanwhile, in Mojokerto District, the stunting prevalence was 27.4%, above the stunting prevalence in East Java province. The local government agency at a regency/municipality level up to a village level plays a role as a policy creator and an implementor; they need to know well about various matters related to stunting to achieve the goal, which is decreasing the stunting rate. This activity aimed to improve the stakeholders’ knowledge as the policymakers on stunting and its preventive efforts. The method used in this study was a cross-sectional method using a quantitative survey. The activity consisted of three stages: first, distributing pre-test questionnaires related to materials that would be given; second, conducting education to the stakeholders by three speakers and was followed by a discussion; third, distributing post-test questionnaires to measure the respondents’ understandings of the education that had been given. The findings of this study indicated that there was a significant difference in the average knowledge of stunting dan the preventive efforts before and after conducting education to the stakeholders (P=0.00). This result showed that there was a positive effect on giving education to improve the stakeholders’ knowledge of stunting as an acceleration effort to the Desa EMAS (Eliminasi Stunting) in Mojokerto District. Keywords: Education, Stunting Knowledge, Stakeholder